ACCESS RITUAL IN EASTERN SUMBA, INDONESIA - B. Retang Wohangara (Celt: A Journal of Culture, English Language Teaching & Literature, 2013)
As a particular type of tradition, rituals have been of interest to folklorists and anthropologists. Understood as repeated, patterned, and contextualized performances, rituals could be in "low contexts" meaning that they are less formally, unplanned in advance, and. do not demand for complicated performances, or in "high contexts" that they are realized in a highly stylized and formalized occasions, and set as public events. This article attempts to describe an access ritual, called paariyangu (ritual of being a guest and a host), conducted by the people of (eastern) Sumba living in the east part of Indonesia. Visiting somebody's house is an act of entering somebody else's private domain. It is therefore necessary for the both parties (i.e. the guest and the host) to abide to certain manners so as to maintain a desirable social encounter. Key words: access ritual, Sumba, traditions, low contexts, high contexts